SHORT-RANGE DISORDER IN POLYELECTROLYTES: REPLICAS AND CONSTRAINED ANNEALING COMPARISON - Mamasakhlisov, A.Ye. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
The general formalism describing polyelectrolyte behavior in presence of sequence disorder is presented. The Edwards and Poisson–Boltzmann equations are obtained. The possible effect of the boundary conditions is discussed. Comparison between replica and constrained annealing approaches is made.
Keywords: polyelectrolyte; DNA; RNA; replicas; constrained annealing